Tender Loving Care Home (TLCH) / Nik Wan Noor Zumi W.Ramli ... [et al.] - W.Ramli, Nik Wan Noor Zumi; Mohd Jamil, Milfadzhilah; Md.Yusak, Noorhayate; Abd. Rahim, Anisah; Mohd Yusof, Maya Emelia (Faculty of Office Management & Technology, 2001)
We have decided to open a sophisticated private old folks home at Kanchong Darat, Banting Selangor. Our General Manager owns this land. It takes about one hour from Klang and two hours from Kuala Lumpur to get there. We have chosen Tender Loving Care Home (TLC Home) as our company name, related to our mission to care and love of people and suitable with our company slogan u Love under one roof ". We will commence our businesses on January 2003 with the capital RM500, 000.00 as agreed of our shareholders. Our target customer is people aged 60 and above around Klang Valley.